2021
DOI: 10.1038/s41419-021-04059-y
|View full text |Cite
|
Sign up to set email alerts
|

Circ-SIRT1 inhibits cardiac hypertrophy via activating SIRT1 to promote autophagy

Abstract: Mounting studies have substantiated that abrogating autophagy contributes to cardiac hypertrophy (CH). Sirtuin 1 (SIRT1) has been reported to support autophagy and inhibit CH. However, the upstream regulation mechanism behind the regulation of SIRT1 level in CH remains unclear. Circular RNAs (circRNAs) are vital modulators in diverse human diseases including CH. This study intended to investigate the regulatory mechanism of circRNA on SIRT1 expression in CH. CH model was established by angiotensin II (Ang II) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“… 4 Some in vivo studies have suggested that SIRT1 overexpression can alleviate Ang II-induced cardiac hypertrophy by reducing cardiomyocyte apoptosis and promoting autophagy. 498 , 499 In addition, SIRT1 overexpression can ameliorate cardiac hypertrophy induced by phenylephrine by inhibiting protein kinase C (PKC)‐ζ activation. 500 However, some studies have shown the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Some in vivo studies have suggested that SIRT1 overexpression can alleviate Ang II-induced cardiac hypertrophy by reducing cardiomyocyte apoptosis and promoting autophagy. 498 , 499 In addition, SIRT1 overexpression can ameliorate cardiac hypertrophy induced by phenylephrine by inhibiting protein kinase C (PKC)‐ζ activation. 500 However, some studies have shown the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al also described that USP22 protects against myocardial ischemia–reperfusion injury via the stabilization of SIRT1 51 . Similarly, Wang et al demonstrated that USP22‐induced deubiquitination of SIRT1 inhibits Angiotensin II or transverse aortic constriction induced cardiac hypertrophy 52 . In the present work, we identified that activation of Flt3 is capable of upregulating SIRT1 protein expression in vivo and in vitro, but we are not sure whether the activation of Flt3 induces expression of USP22 in the setting of our current work, thus leading to deubiquitination of SIRT1 and its upregulation, so more work is needed.…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, in their study, ceRNA network play an important role in pathogenesis of cardiac hypertrophy. Circ-SIRT1 bound with miR-3681-3p and miR-5195-3p to regulate SIRT1 expression post-transcriptionally ( Wang et al, 2021 ). In another study, Wu et al indicated that circ Yap is a critical regulator in cardiac fibrosis in the pressure overload mouse model ( Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%